2018
DOI: 10.1177/2165079918795958
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Skin Disorders Among Health Care Workers

Abstract: This study aimed to estimate the point prevalence and 1-year period prevalence of skin disorder symptoms (SDS) among health care workers (HCWs) and to explore the possible risk factors. A random sample of 400 HCWs from 13 government health centers in Brunei Darussalam self-administered an adapted Nordic Occupational Skin Questionnaire (NOSQ-2002/SHORT). The point and 1-year prevalence of SDS were 12% and 19%, respectively. Having a history of SDS before the current job, exposure to SDS-exacerbating materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Through our research, we observed that several Asian countries, including Malaysia, Thailand, China, and Brunei, participated in their respective studies to identify the prevalence of HD among HCWs. A total of three studies [ 9 , 10 ] were conducted in Thailand surveying the prevalence of HD and reported an average prevalence of HD of 16.77%. The prevalence of HD was 6.75% in China [ 11 ] and 25.20% in Malaysia [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through our research, we observed that several Asian countries, including Malaysia, Thailand, China, and Brunei, participated in their respective studies to identify the prevalence of HD among HCWs. A total of three studies [ 9 , 10 ] were conducted in Thailand surveying the prevalence of HD and reported an average prevalence of HD of 16.77%. The prevalence of HD was 6.75% in China [ 11 ] and 25.20% in Malaysia [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Apart from a country-based analysis, a study [ 9 ] in Thailand examined the prevalence of HD among HCWs in nonclinical and clinical departments and reported a significant difference between the two groups. The glove-related HD percentage was 11.0% among the HCWs in the nonclinical department and 24% among those in the clinical department.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have indicated that medical workers are susceptible to infectious and parasitic diseases [ 3 , 4 ]; neoplasms [ 5 , 6 ]; endocrine diseases, nutritional diseases, metabolic and immune diseases [ 7 , 8 ]; psychosis [ 9 , 10 ]; neurological disorders and eye and adnexa diseases [ 11 , 12 ]; diseases of the circulatory system [ 6 , 12 ]; diseases of the respiratory system [ 13 , 14 ]; digestive diseases [ 15 , 16 ]; diseases of the genitourinary system [ 15 ]; diseases of the skin and subcutaneous tissue [ 17 , 18 ], and diseases of the musculoskeletal system and connective tissue [ 19 , 20 , 21 ]. Many risk factors have been associated with medical workers to develop systemic diseases, such as occupation [ 6 , 22 ], gender [ 23 ], age [ 24 ], work experience, Charlson comorbidity index [ 16 ], payroll bracket, medical institution class [ 25 ], medical institution ownership, division of the National Health Insurance Administration, and degree of urbanization [ 26 ].…”
Section: Introductionmentioning
confidence: 99%